THE EFFECTS OF ETHICS ON MORAL HAZARD IN BUSINESS MANAGEMENT MODERATED BY CORPORATE GOVERNANCE: A LITERATURE REVIEW - Andy Ismail; Hendri Dwi Dwi Purnomo; Muhammad Arifin; Syavergio Avia Difaputra; Hunik Sri Runing Sawitri (Profetika: Jurnal Studi Islam, 2023)
Ethics was a significant aspect based on violation of the central manager. A moral hazard situation happens when an individual has a bigger tendency to take risks caused by the individual potential that appears to bear the risks. Many scandals involving accountants have appeared in headlines within these few weeks since they lost their morals, some reasons that made the corporates critical to obey norms and certain ethical standards. This scandal has increased scepticism for those who were already critical of their professional work and ethical integrity. In recent decades, moral hazard has become a hot and crucial issue in corporations, especially in Indonesia. This research method is a qualitative type with a descriptive phenomenological approach and literature review. The results of the study concluded, in running business activity, a company should avoid negative activities by practising appropriate business ethics and good corporate governance.